Reversible destiny : mafia, antimafia, and the struggle for Palermo - Schneider, Jane, 1938- (University of California Press, 2003)
Reversible Destiny traces the history of the Sicilian mafia to its nineteenth-century roots and examines its late twentieth-century involvement in urban real estate and construction as well as drugs. Based on research in the regional capital of Palermo, this book suggests lessons regarding secretive organized crime: its capacity to reproduce a subculture of violence through time, its acquisition of a dense connective web of political and financial protectors during the Cold War era, and the sad reality that repressing it easily risks harming vulnerable people and communities.